(untitled) (Research, Society and Development, 2022)
The objective of the research was to analyze the use of the Mobile System for Elderly Monitoring (Sistema Móvel de Assistência ao Idoso, SMAI) in the care of people with dementia through the messages exchanged between family caregivers and health professionals. This is a qualitative study, based on a descriptive phenomenological framework, on the experience of using the SMAI application in the production of care in a geriatrics and gerontology service. Data were analyzed using the IRAMUTEQ software and Descending Hierarchical Classification technique to estimate the frequency of words by classifying text segments according to vocabularies and lexical analysis of words. Statistical analyzes were carried out on two textual corpus, one of which was the result of messages sent by caregivers and the other with the answers of health professionals. Thirty-four family caregivers of people with dementia and five health professionals participated in the study. The use of the system resulted in the organization of consultations; in the management of behavioral changes; in remote monitoring and care management by the service’s health team, in addition to strengthening the bond and improving communication. The answers of professionals through the application pointed to a demand related to the organization of care for people with dementia at home. The SMAI application worked as an innovative tool for social and assistance support for family caregivers who received guidance on caring for a person with dementia and its specificities. Technological and social transformations can contribute to the development of increasingly innovative health care models. The study opens perspectives for the development of mobile applications that promote comprehensive care for people with dementia and offer a social support network to family caregivers.